TRANSPORT, MAGNETIC AND THERMAL PROPERTIES OF (Fe100-XVX)75 P15C10 SEMIAMORPHOUS RIBBONS - S. Karal, M. A.; Kamruzzaman, M.; M. Hossain, M. G.; Khan, F. A.; I. Jaim, H. M. (The Nucleus, 2011)
(Fe100-xVx)75P15C10 [x=1.5, 3, 9 and 15] semi-amorphous alloys (partially crystalline) in the form of ribbon were prepared by the standard melt spinning technique and studied their transport, magnetic and thermal properties. The nature of the as prepared samples was studied by x-ray diffraction (XRD). The resistivity of the samples was investigated from temperature 93K to 800 K. The resistivity followed ‘Mooij Correlation’ at low temperature (93 K-300 K). The resistivity at higher temperature (300 K-800 K) remained constant upto a certain temperature and then decreased with temperature rise. The Hall resistivity and the magnetoresistance (MR) were measured in an applied magnetic field upto 0.6 T at room temperature (RT=300 K). Anomalous Hall effect was observed in the Hall resistivity measurement and MR was found to vary 0-8%. The saturation magnetization gradually decreases with the increase of the substitution of Fe by V at RT. Both the impedance magnitude and phase angle remained constant upto 106 Hz and then remarkably increased with frequency. The thermal properties associated with crystallization temperature and weight changes were measured by using the differential thermal analyzer (DTA) and the thermo gravimetric (TG) techniques respectively.